On The Possibility Of Living Under Non-Muslim Rule From The Perspective Of Islamic Law - Arangül, Muammer (HITIT UNIVERSITESI ILAHIYAT FAKULTESI DERGISI-JOURNAL OF DIVINITY FACULTY OF HITIT UNIVERSITY, 2017)
As it is in the history, millions of Muslims today live under the rule of non-Muslims. Today, however, this has reached a quantity that is incomparable to the past. Muslims were not willing to legitimize the dominance of non-Muslims for various reasons during periods when they had countries they lived freely and/or in welfare. But as the historical reality begins to turn away from them politically and economically, they have begun to think that this may be possible provided that they comply with some Islamic principles. In my article, I hope that the minds of some Muslims living in non-Muslim countries will be enlightened to a certain extent and to contribute to the solution of the problem, by examining how it is handled in the fiqh literature.
Keywords: Dar al-Islam; Dar Al-Harb; Hijra; Shaair al-Islam; Non-Muslim Rule